Business Activities Using Chatbots - Ionut-Alexandru CIMPEANU (Informatică economică, 2021)
In this article, we present a short introduction about chatbots and we describe two original chatbot solutions used in education and tourism. In the first part of the article, we describe the life cycle of a chatbot, presenting the steps needed for its development. We continue with the enumeration and description of the design techniques that developers are using in making the chatbots. The article also presents the architecture of two original chatbot solutions, the design methods and techniques used in their development and implementation and the usefulness and benefits of these two models. Moreover, possible future improvements of these chatbots for having an increased performance are presented. As a conclusion, we highlight the concern of business people for the use of chatbots in any field of activity and the progress that economic activity registers through their use.